2016
DOI: 10.3233/jad-151090
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophage Transplantation Ameliorates Cognitive Dysfunction in Amyloid-β-Treated Rats Through Regulation of Microglial Polarization

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder in the elderly population. Neuroinflammation induced by amyloid-β (Aβ) aggregation is considered to be the critical factor underlying AD pathological mechanisms. Alternatively activated (M2) macrophages/microglia have been reported to have neuroprotective effects in neurodegenerative disease. In this study, we characterized the neuroprotective effects of M2 macrophage transplantation in AD model rats and investigated the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…These findings suggested that the protective effect might may in part due to the reduced number of M1 cells. M2 macrophages/microglia function as an anti-inflammatory subset, expressing high levels of cytokines such as IL-10 and TGF-β, as well as neurotrophic factors such as nerve growth factor (NGF) 50 and insulin-like growth factor-1 (IGF-1) 51 . These beneficial cytokine and neurotrophic factors participate in neuronal protection and survival.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that the protective effect might may in part due to the reduced number of M1 cells. M2 macrophages/microglia function as an anti-inflammatory subset, expressing high levels of cytokines such as IL-10 and TGF-β, as well as neurotrophic factors such as nerve growth factor (NGF) 50 and insulin-like growth factor-1 (IGF-1) 51 . These beneficial cytokine and neurotrophic factors participate in neuronal protection and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Clearance of Aβ and chronic inflammation are related to the polarization of and phagocytotic ability of microglia (Ide et al, 1996; Heese et al, 1998; Hutchinson et al, 2009; Tang and Le, 2016). The M2 phenotype microglia have been demonstrated to have a neuroprotective function in AD (Zhu et al, 2016). A recent study showed that M2 macrophage transplantation reduces neuroinflammation in the brain, promotes clearance of Aβ, and improves cognitive impairment (Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The M2 phenotype microglia have been demonstrated to have a neuroprotective function in AD (Zhu et al, 2016). A recent study showed that M2 macrophage transplantation reduces neuroinflammation in the brain, promotes clearance of Aβ, and improves cognitive impairment (Zhu et al, 2016). Aβ and tau oligomers activate M1 pro-inflammatory responses and induce irreversible neuron loss (Tang and Le, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no clinical effects of anti-inflammatory treatment were observed in clinical trials [42,43,44]. According to the recent knowledge on microglia polarization, promoting M2-microglia phenotype may be a promising target, as shown by studies on preclinical models of stroke [45], TBI [46], AD [47], PD [48], ALS [49], and multiple sclerosis (MS) [50]. Nonetheless, targeting neuroinflammation in these diseases is even more complex and a regimen of anti-inflammatory treatments is also crucial.…”
Section: Involvement Of Activated Microglia In Brain Disordersmentioning
confidence: 99%